ANALISIS NILAI TAMBAH AGROINDUSTRI KERUPUK AMPLANG UDANG DI KELURAHAN PULAU KIJANG KECAMATAN RETEH - Kurniawan, Wawan; Hadi, Syaiful; Dewi, Novia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Shrimp-based agroindustry is one of the efforts made in the Kijang Island District, Reteh District. Shrimp processing agro-industry becomes shrimp amplang crackers, the existence of this agro-industry is expected to improve quality, profitability and added value. The purpose of this study was to analyze the added value of the amplang shrimp cracker agroindustry in Kijang Island Village, Reteh District. The method of taking respondents was carried out in a census where the total population in the Kijang Island District, Reteh Subdistrict, was made as a respondent by 7 business actors in shrimp amplang crackers. The technique of data collection is done by direct interviews with respondents and analysis of data using the Hayami value-added analysis method. The results showed that the profit received from the Amplang shrimp cracker agroindustry business was Rp. 12,471.43 per kg. Shrimp amplang cracker agroindustry added value of Rp. 18,876.10 per kg. The profit obtained in one production process is Rp. 12,471.10 per kg of raw material. And every kilogram of raw material produces a margin of Rp. 18,976.10 consisting of labor income, other input contributions and profits of business actors.Keywords: Agroindustry, Shrimp, Sand, Crackers, Value added